Kewenangan Judicial Review Undang-Undang oleh Mahkamah Konstitusi dalam Sistem Negara Hukum Indonesia - Risman Setiawan (INDO PUBLISHING, 2025)
Indonesia is a state based on the rule of law. This requires that all governmental processes and legal products, including laws, must comply with the constitution as the highest legal norm. The authority of the Constitutional Court to conduct judicial review of laws against the 1945 Constitution of the Republic of Indonesia is a concrete manifestation of a systematic recognition of the principle of constitutional supremacy, the protection of citizens' rights, and the strengthening of checks and balances among state institutions. Therefore, the judicial review authority held by the Constitutional Court holds a highly strategic position within Indonesia's legal system and is fully aligned with the principles of the rule of law.